Conteúdo de oxigênio no atlântico tropical sudoeste - RODRIGUES, Julia Galetti (2022)
The Southwestern Tropical Atlantic (SWTA) is considered well oxygenated by the NBUC/NBC current system. Still, given the ongoing increase in ocean deoxygenation in the Eastern Tropical Atlantic (ETA), it is important to improve the knowledge on the current state of oxygen content in the SWTA. In this sense, we present the first three-dimensional representation of dissolved oxygen (DO) in the SWTA. Functional Data Analysis (FDA) was used to construct a database of DO profiles from two surveys (austral spring of 2015 and autumn of 2017) and complementary data from Pangea database. Results depicted three spatial areas with distinct oxygen content patterns, directly linked to the current systems: (i) Western Boundary Current System (WBCS) area, characterized by well oxygenated waters; (ii) South Equatorial Current System (SECS) area, containing the lowest DO values among all, and (iii) transition zone area, with intermediate DO content. We reveal that while the water column is fully oxygenated in the NBUC/NBC, WBCS oxygen content decreases at the limit of core as close as ~91 km (~50 km) from the coast in spring (autumn), due to the seasonal variability in NBUC/NBC intensity. Results also indicated that some processes are acting on the oxygen content in the study area, suggesting that the influence of the variability of the NBUC connection to the SEUC flow may feed subsurface westward transport of DO rich waters. Furthermore, a seasonal latitudinal displacement of the SEUC core could influence the distribution of the observed low oxygen waters, as well as allow the NBUC retroflection to occur. Lastly, these findings highlight the importance of the western boundary current in maintaining the oxygenation and keeping the westward advected deoxygenated waters from reaching the shore.